2013
DOI: 10.1590/s0100-40422013000900015
|View full text |Cite
|
Sign up to set email alerts
|

Preparative separation of C19-diterpenoid alkaloids from Aconitum carmichaelii Debx by pH‑zone-refining counter-current chromatography

Abstract: Recebido em 28/3/13; aceito em 27/6/13; publicado na web em 21/8/13The technique of pH-zone-refining counter-current chromatography was successfully applied to preparatively separate three C 19 -diterpenoid alkaloids from the crude extracts of Aconitum carmichaelii for the first time using a two-phase solvent system of petroleum ether-ethyl acetate-methanol-water (5:5:1:9, v/v/v/v). Mesaconitine (I), hypaconitine (II), and deoxyaconitine (III) were obtained from 2.5 g of the crude alkaloids in a one-step separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…At present, a comparison of metabolic profiles has revealed that three major groups of alkaloidsamine diterpenoid alkaloids (ADAs), diester diterpene alkaloids (DDAs), and lipoalkaloidsare present in the roots of Aconitum. They share a common C19-norditerpenoid skeleton, in which the C8 position is occupied by a hydroxyl, an acetoxy or a fatty acid acyl group, respectively (Hu et al, 2009;Liu et al, 2011;Xu et al, 2011;Kawasaki et al, 2011). The toxicity of Aconitum derives mainly from the DDAs, including aconitine, mesaconitine and hypaconitine (Lu et al, 2010).…”
Section: Analysis Of Metabolic Biomarkersmentioning
confidence: 99%
“…At present, a comparison of metabolic profiles has revealed that three major groups of alkaloidsamine diterpenoid alkaloids (ADAs), diester diterpene alkaloids (DDAs), and lipoalkaloidsare present in the roots of Aconitum. They share a common C19-norditerpenoid skeleton, in which the C8 position is occupied by a hydroxyl, an acetoxy or a fatty acid acyl group, respectively (Hu et al, 2009;Liu et al, 2011;Xu et al, 2011;Kawasaki et al, 2011). The toxicity of Aconitum derives mainly from the DDAs, including aconitine, mesaconitine and hypaconitine (Lu et al, 2010).…”
Section: Analysis Of Metabolic Biomarkersmentioning
confidence: 99%
“…More recently, three C 19 -diterpenoid alkaloids were isolated from the lateral roots of Aconitum carmichaeli Debx by CCC [27]. However, there is no article gthus far reporting the separation of C 19 -diterpenoid alkaloids from A. duclouxii by CCC.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, many studies have been published, reporting the successful use of CCC for the separation and purification of C 20 ‐ and C 18 ‐diterpenoid alkaloids from genus aconitum . More recently, three C 19 ‐diterpenoid alkaloids were isolated from the lateral roots of Aconitum carmichaeli Debx by CCC . However, there is no article gthus far reporting the separation of C 19 ‐diterpenoid alkaloids from A. duclouxii by CCC.…”
Section: Introductionmentioning
confidence: 99%